Globalisasi, Liberalisasi Ekonomi dan Krisis Demokrasi - Puji Rianto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
Different from the advocates of neoliberalism, this article argues that economic globalization not only fails to create prosperity but also fails to build democratic political system. Globalisation has brought profound change on the role of multinational corporations. Rather than brought equality, globalization has widen the gap between the poor and the rich which prohibites democratization. Globalisation has brought the power of MNCs to direct many public policies in underdeveloped countries which brings advantage to MNCs.